Między politologią i komunikologią - Bogusława Dobek-Ostrowska (Ksiegarnia Akademicka Publishing, 2021)
Between Political Science and Media Studies. Together or Separately? Case of Studies Dedicated to Political and Media Systems in Central and Eastern Europe